2011
DOI: 10.1089/rej.2011.1178
|View full text |Cite
|
Sign up to set email alerts
|

Combined Exercise and Insulin-Like Growth Factor-1 Supplementation Induces Neurogenesis in Old Rats, but Do Not Attenuate Age-Associated DNA Damage

Abstract: We have investigated the effects of 2 weeks of insulin-like growth factor-1 (IGF-1) supplementation (5 mg/kg per day) and 6 weeks of exercise training (60% of the maximal oxygen consumption [VO 2 max]) on neurogenesis, DNA damage/repair, and sirtuin content in the hippocampus of young (3 months old) and old (26 months old) rats. Exercise improved the spatial memory of the old group, but IGF-1 supplementation eliminated this effect. An age-associated decrease in neurogenesis was attenuated by exercise and IGF-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 95 publications
1
36
2
1
Order By: Relevance
“…In addition, it seems that observed changes in OGG1 and 8-OHdG are simply due to HIIT protocol. While two previous studies have been reported that running (Koltai et al, 2011) and swimming (Ogonovszky et al, 2005b) with low to moderate intensity have no significant influence on OGG1 and 8-OHdG levels in rat's hippocampus, our findings show an increase in OGG1 contents of brain and liver following HIIT. Our findings are supported by a study by Ogonovszky et al (2005), who reported an increase in OGG1 activity and 8-OHdG levels of rat liver following strenuous and overtraining (Ogonovszky et al, 2005a).…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…In addition, it seems that observed changes in OGG1 and 8-OHdG are simply due to HIIT protocol. While two previous studies have been reported that running (Koltai et al, 2011) and swimming (Ogonovszky et al, 2005b) with low to moderate intensity have no significant influence on OGG1 and 8-OHdG levels in rat's hippocampus, our findings show an increase in OGG1 contents of brain and liver following HIIT. Our findings are supported by a study by Ogonovszky et al (2005), who reported an increase in OGG1 activity and 8-OHdG levels of rat liver following strenuous and overtraining (Ogonovszky et al, 2005a).…”
Section: Discussioncontrasting
confidence: 93%
“…OGG1, as main repair enzyme, expresses in all kinds of tissues with significantly different levels, recognizes and cleaves 8-OHdG from DNA (Ogonovszky et al, 2005a). There is now evidence that age (Radak et al, 2011), smoking (Park et al, 2011, VO 2 max (Loft et al, 1994), physical labor, BMI, inter-individual variation, nutrient (Kasai et al, 2001) and mental state, especially clinical depression (Forlenza et al, 2006), all affect OGG1 levels. Therefore, animal models were used in the present study to control the variables mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations